Sah (الصحة) dan Batal (البطلان) Menurut Ulama Usul Fiqh: Validity and Invalidity According to Scholars of Islamic Jurisprudence Principle - Kamarul Zaman, Muhammad Akramin (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2017)
Man is created by Allah in order to submit to Him. Thus, Allah revealed the Qur’an as a guide accompanied by the prophetic traditions of the Prophet SAW that clarify the meanings of the Quran on matters that are related to Islamic personal practices as well as rules which govern human interactions in their daily life. The said rules that are included in the Quran and prophetic traditions cover, among others requirements as well as guidelines for Muslims to ensure the validity (or invalidity) of their daily practices. The Muslim scholars had explained the meanings of validity and invalidity as well as the differences between invalidity and fasad according to Quran and prophetic traditions so as to guide the Muslims to understand Islamic practices as well as human interactions according to Islam. The study on the books of Islamic jurisprudence school of thought found that there were different opinions regarding the meaning of invalidity and fasad among the scholars from different schools.